Effects of bacteriophages on gut microbiome functionality - Elena Kurilovich; Naama Geva-Zatorsky (Gut Microbes)
The gut microbiome, composed of bacteria, fungi, and viruses, plays a crucial role in maintaining the delicate balance of human health. Emerging evidence suggests that microbiome disruptions can have far-reaching implications, ranging from the development of inflammatory diseases and cancer to metabolic disorders. Bacteriophages, or “phages”, are viruses that specifically infect bacterial cells, and their interactions with the gut microbiome are receiving increased attention. Despite the recently revived interest in the gut phageome, it is still considered the “dark matter” of the gut, with more than 80% of viral genomes remaining uncharacterized. Today, research is focused on understanding the mechanisms by which phages influence the gut microbiota and their potential applications. Bacteriophages may regulate the relative abundance of bacterial communities, affect bacterial functions in various ways, and modulate mammalian host immunity. This review explores how phages can regulate bacterial functionality, particularly in gut commensals and pathogens, emphasizing their role in gut health and disease.